African American Undergraduate Students’ Perceived Welcomeness at a Midsized University Library - Kirstin Duffin; Ellen Corrigan (Evidence Based Library and Information Practice, 2023)
Objective – This project assessed African American students’ feelings of comfort and belonging about engaging with library resources and services at a public regional comprehensive university in the midwestern United States.